Методичні підходи до планування бізнес-процесів в електронній комерції - Василичев, Д. В.; Vasylychev, D. (ЦНТУ, 2017)
В статті проведено дослідження методичних підходів до планування бізнес-процесів в електронній комерції. Доведено, що залишаються невирішеними ряд теоретичних і методологічних питань, які пов'язані з розробкою сучасних моделей, принципів і методів планування в системі електронної комерції. Обґрунтована необхідність здійснення процесу планування розвитку бізнесу для забезпечення ефективної організації електронної комерції. Запропоновано уточнене визначення електронної комерції та комплекс стратегій розвитку бізнесу для підприємств, які планують впроваджувати інноваційні технології електронної комерції. Research of methodological approaches to the planning of business processes in e-commerce was performed in the article. Literature analysis has shown that there is still a number of methodological and theoretical questions which are still unresolved, the issues are connected with development of modern models, principles and methods of planning in the system of e-commerce. In the research some definitions of category “electronic commerce” are presented. In general, it is economical process of goods and services exchange on the basis of existing partnership with the help of electronic methods of communication. According to the author’s opinion, electronic commerce envisages making an agreement with the help of electronic exchange of information and other electronic ways of transferring data. To electronic agreements can be related agreements which are made and performed using electronic devices of connection and modern information communicational systems and nets. In a generalized form, it was proposed for enterprises which are planning to introduce innovative technologies of electronic commerce, to use the following strategies of business process development: micro targeting of on-line audience, personalization, creation of content for attraction, creation of site for target segment, integration through the channels, investment to the mobile commerce, attention to logistics, using of trade with the possibility of subscriptions, beating of competitors, proposition of work convenience through other channels, selection of property, selling only via Internet shop. Proposed strategies of electronic commerce can be used by multiple enterprises to plan business processes.
Methodical approaches to business process planning in e-commerce
Keywords: електронна комерція; інновації; планування; бізнес-процес; стратегії; e-Commerce; innovation; planning; business process; strategy